Experimental Investigation On Indirect, Natural And Forced Convection Mixed Mode Solar Dryer - Misha, Suhaimi; Ahmed Al-Qadhi, Ahmed Abdullah; Mohd Rosli, Mohd Afzanizam; Yusof, Ahmad Anas (International Journals of Engineering and Sciences Publisher, 2018)
The installation of solar drying systems have been constantly developed in the last few years to acquire better effective results and drying performance.Baes on the previous designs,It might be concluded that the efficiency of the solar dryers is essentially depends on the thermal distribution and uniformity of flow inside the dryer chamber.There are various types of solar dryers that have been developed and they are classified based on the mode of air circulation (natural circulation and forced circulation),or based on the type of drying such as,direct solar drying,indirect solar drying and mixed mode solar drying etc. Several solar dryers have been utilized recently,however,they do not perform well in terms of high temperature and air distribution throughout the dryer which negatively affects the efficiency of the dryer.Moreover,relying on a single mode of these drying system might not provide the optimum results.Therefore,in this study a conceptual devise of a mixed mode solar dryer which includes direct,indirect,and forced convection solar drying is proposed and fabricated.An experimental investigation is performed on this device using an automated recording to plot the temperature profile at diverse positions in the dryer.This testing was conducted at five different stated of the dryer to attain the most suitable method for drying based on the resulted temperature and velocity.From the results of the experiments it can be concluded that the mixed mode solar dryer with forced convection is recommended among other states.